Edukasi Keselamatan Lalulintas Warga Ngadinegaran Kecamatan Mantrijeron Daerah Istimewa Yogyakarta - anita rahmawati (Universitas Lancang Kuning, 2021)
The community service program is carried out in Ngadinegaran, Mantrijeron, DIY. Mantrijeron Urban Village is in the Mantrijeron sub-district area with an area of ​​2.61 km2. Kampung Ngadinegaran is part of the tourist center in the city of Yogyakarta, with high population and during holidays the road conditions also become very crowded and even congestion often occurs. This highly congested traffic condition often causes accidents due to lack of knowledge of traffic safety. The target of this activity is to improve understanding, awareness and knowledge of traffic safety, so that the number of accidents that occur will be reduced. The method in this commuty service is to provide socialization about the importance of traffic safety . The result of socialization shows that the community is very interested in this activity and they want to get more information about traffic safety education regularly because this activity can improve the awareness about traffic safety.